Cover image. Issue 6 (June 2017) - Finot, F.; Kaddour, A.; Morat, L.; Mouche, I.; Zaguia, N.; Cuceu, C.; Souverville, D.; Négrault, S.; Cariou, O.; Essahli, A.; Prigent, N.; Saul, J.; et al.
Abstract : The cover image, by F. Finot et al., is based on the Research Article Genotoxic risk of ethyl‐paraben could be related to telomere shortening, DOI10.1002/jat.3425 .